Tissue expansion: Concepts, techniques and unfavourable results - Milind S Wagh; Varun Dixit (Indian Journal of Plastic Surgery)
The phenomenon of tissue expansion is observed in nature all the time. The same properties of the human skin to stretch and expand and yield extra skin if placed under continuous stress over a prolonged period of time has been utilised for reconstructive purposes with the help of a silicon balloon inserted under the skin and progressively filled with saline. The technique of tissue expansion is now more than three decades old and has been a value addition to our armamentarium in reconstructive surgery in all parts of the body. However, it still requires careful patient selection, meticulous planning and faultless execution to successfully carry out the process, which usually lasts for more than 8-12 weeks and involves two sittings of surgery. Any compromise in this process can lead to unfavourable results and complications, some minor, which allow continuance of the process to attain the expected goal and others major, which force abandonment of the process without reaching the expected goal. This article seeks to highlight the intricacies of the concept of tissue expansion, the technique related to flawless execution of the process and likely complications with emphasis on their management. We also present our results from a personal series of 138 patients operated over a period of 18 years between 1994 and 2012.